ASSOCIATION OF PERCEIVED PARENTING STYLES, PSYCHOLOGICAL DISTRESS AND RESILIENCE AMONG ADOLESCENTS WITH DEAFNESS: A CORRELATIONAL STUDY (Contemporary Journal of Social Science Review, 2025)
Objectives: The study was undertaken to determine the association of perceived parental styles on the psychological distress of adolescents with deafness. Further, study investigates the association of resilience with psychological distress among adolescents with deafness. Sample and Method: Sample comprise of 100 adolescents (male = 50, female = 50). ages between 12-18 years. A convenient sampling method was used to collect data from different Special Education Schools situated in Lahore, Punjab. The Parental Authority Questionnaire (PAQBuri, 1991), Kessler Psychological Distress Scale (K10; Kesler, 2002), and Ego-Resiliency Scale (ERS; Block & Kreman, 1996) were used. Results: The results indicate that parenting styles i.e., authoritarian parenting style (r = .99, p